Corps martyrisés, corps sanglants, corps dépecés : le Perlesvaus, ancêtre du gore ? - Armand Strubel (Revue des Langues Romanes)
The novel commonly known as Perlesvaus, which calls itself the Haut Livre du Graal, disconcerts the lector by a dramatic accumulation of acts of barbarism and a taste for horrible detail. By the theatricalization of an outrageous violence (innumerable cut heads, mutilated corpses, tank of blood where knights are drowned…), this cruel tale asks us how close this imaginary is to the modern gore. But the excesses of hemoglobin, apart from rare moments of aesthetic fascination for games of color, testifie to a dialectic between matter–an archaic imagery, violent even sadistic–and senefiance. A rhetoric of enargeia that rests on the bloody exhibition, aims to arouse piety, as shown by the recurring appearance of the blood of Christ. From then on, the vision of blood is both a sign of the sacred and a way of catharsis. The bloody violence of the Old Law is sublimated by compassion, and the chivalrous adventure takes a sacrificial form.